Impact of shoulder injuries on quality of life for retired National Basketball Association players: A survey study - Gohal, C.; Khan, M.; Burrus, T.; Madden, K.; Gagnier, J.; Rogowski, J. P.; Bedi, A. (International Journal of Sports and Exercise Medicine, 2019)
Background: Athletes in the National Basketball Association (NBA) are at risk of sport-related injuries due to the frequent jumping, pivoting, and overhead movements that constantly strain the musculoskeletal system. A comprehensive understanding of how shoulder injuries affect athletes during their NBA careers and into retirement has not been studied. Purpose: The purpose of this study is to utilize a survey to evaluate the epidemiology of shoulder injuries in NBA players and determine the impact that these injuries have on post-retirement function and Health-Related Quality of Life (HRQOL). Study design; Cross-sectional survey. Methods: A survey encompassing demographic characteristics, injuries prior to and during a player's NBA career, and post-retirement Tegner Activity Levels and HRQOL as per the EQ-5D was developed and validated by a specialized focus group. It was distributed to all retired members of the National Basketball Players Association (NBPA) electronically through the SurveyMonkey platform, from which data was abstracted and analyzed. Descriptive statistics were used for means and proportions, dichotomous variables were compared with chi-squared test, continuous variables were compared with student's t-test, and non-parametric data was compared with Mann-Whitney U test. A multiple regression analysis was performed to assess for potential factors correlated to injury. Results: One hundred eight retired NBA players participated in the survey, with the majority being over the age of 55 (72.2%, range 35-55+). A quarter of respondents (27.6%) reported having a shoulder injury during their NBA career, most commonly shoulder dislocation (37.9%) and acromioclavicular joint injury (37.9%). Of those injured players, 72.4% continued to have shoulder pain until retirement. Over half of all respondents, (51.9%) report current shoulder pain in the post-retirement period, which has significantly impaired their Tegner Activity Level (p = 0.003) and QOL as per the Visual Analog Scale (p < 0.00004). Conclusion: A significant number of professional basketball players report shoulder injury during career, most commonly shoulder instability and AC joint injury. The majority of respondents continue to report pain until retirement. Post-retirement shoulder pain significantly impairs activity levels and HRQOL. Further evidence is needed to identify the risk factors for post-retirement shoulder pain to help guide clinicians in managing and counseling professional basketball players.